2011
DOI: 10.1590/s0102-311x2011001500005
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and the risk of incident hypertension in a population of community-dwelling Brazilian elderly: the Bambuí cohort study of aging

Abstract: (RR = 0.54;). Other lipid parameters had no significant effect on the outcome. High HDL-cholesterol showed an independent protective effect on subsequent development of hypertension in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…As for medications for the alimentary tract and metabolism, there was an increase of 2.6 times in the prevalence of drugs used in diabetes, which is consistent with the increase in the prevalence of diabetes mellitus among the older elderly in the Bambuí cohort 34 . Meanwhile, there was a decrease in the use of vitamins in the more recent cohort as compared to the earlier.…”
Section: Discussionsupporting
confidence: 71%
“…As for medications for the alimentary tract and metabolism, there was an increase of 2.6 times in the prevalence of drugs used in diabetes, which is consistent with the increase in the prevalence of diabetes mellitus among the older elderly in the Bambuí cohort 34 . Meanwhile, there was a decrease in the use of vitamins in the more recent cohort as compared to the earlier.…”
Section: Discussionsupporting
confidence: 71%
“…Due to its complex and multifactorial nature, the prevention of dyslipidemia must refer to multiple risk factors. Evidence showed that some predictors are associated with the occurrence of dyslipidemia [7]. Factors related to diet, lifestyle and family history might be associated with an increased risk of dyslipidemia [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…HDL-C level has been shown to be an independent factor and to be inversely associated with incident hypertension. 6,7,[26][27][28] A study with 15 000 subjects showed that lower level of HDL-C appears to precede the development of hypertension by at least 3 years. 28…”
Section: Discussionmentioning
confidence: 99%